Analysis of the hydrological characteristics of the Tanjiro River Basin - Nagy , Zahraa; AlIbrahimi, Suhaila (Al-Adab Journal, 2024)
After identifying the morphometric characteristics of the Tanjiro Basin and its secondary basins and the natural situation of the region, it became necessary to study the hydrological characteristics of the basin because it has important hydrological indications about the drainage basins, as it is a reflection of the climatic and topographical conditions of the basins in the study area, and the study of these characteristics contributes to predicting the amount of water flow The streams of the basin, which are important in determining the possibility of water harvesting in the basin, its quantity and investments on the one hand, and preventing flood risks on the other hand. importance in determining the extent of benefiting from water in the field of development and human uses. ‏